Reporting practices in applied linguistics quantitative research articles across a decade: A methodological synthesis - Marefat, Fahimeh; Hassanzadeh, Mohammad; Noureddini, Sina; Ranjbar, Mostafa (System (Linköping), 2025)
The standards for quantitative second language (L2) research paradigm are becoming increasingly stringent. Meanwhile, the purpose of methodological synthesis is to describe, examine, and appraise field-wide practices to augment the quality of future research. The current study strove to follow this line of inquiry by examining study quality and reporting practices in 382 experimental research articles (RAs) from seven international journals with an eye to any evolving pattern over time. In so doing, an integrated-moderated coding scheme was created. Then, the frequency counts and all related practices for the period between 2011 and 2021 were documented. The overall analysis revealed substantial adherence to methodological quality standards, including the reporting of sample size, pretesting, as well as descriptive and inferential statistics. Nevertheless, issues such as inadequate integration of probability sampling, delayed posttesting, advanced statistical techniques, and data-accountable graphs were evident as well, albeit slightly improving over time. Findings are expected to enhance the methodological awareness of L2 researchers as well as those who aspire to adopt a holistic and collaborative approach to methodological syntheses.